2013
DOI: 10.1007/s00408-013-9511-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training on Sleep Apnea: A Meta-analysis

Abstract: Background Several studies have shown a favorable effect of supervised exercise training on obstructive sleep apnea (OSA). This meta-analysis was conducted to analyze the data from these studies on the severity of OSA (primary outcome) in adults. Secondary outcomes of interest included body mass index (BMI), sleep efficiency, daytime sleepiness and cardiorespiratory fitness. Methods Two independent reviewers searched PubMed and Embase (from inception to March 6, 2013) to identify studies on the effects of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
138
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(157 citation statements)
references
References 52 publications
14
138
1
4
Order By: Relevance
“…This finding was expected, because of the physical activity increase and the calorie reduction. The effect of physical exercise on OSA was alredy described even with minimal body weight change [7], and may futher improve once a more consistent body weight reduction will be achieved [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was expected, because of the physical activity increase and the calorie reduction. The effect of physical exercise on OSA was alredy described even with minimal body weight change [7], and may futher improve once a more consistent body weight reduction will be achieved [16].…”
Section: Discussionmentioning
confidence: 99%
“…The exercise training was found effective on OSA [7] either as such or in relation to the reduction of the energy intake [8], even without the need of using the continuous positive air pressure (CPAP) [9]. The body weight (BW) reduction can also improve the OSA symptoms, even though it is very difficult to keep the patients on a diet for long period of time.…”
Section: Introductionmentioning
confidence: 99%
“…Third, a recent meta-analysis suggests that physical training might be effective in reducing sleep apnea severity independently of weight loss [50]. Thus, specific programs might be identified for OSA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although there were many studies that examined the relationship between sleep quality and physical activity, exercise and obesity, most of them focus on overall fitness or only one component of physical fitness (Tworoger et al, 2003;Lee and Lin, 2007;Reid et al, 2010;Iftikhar et al, 2014). Currently while teachers" in secondary (SMK) schools, reported sleep problems among students are common and it diminishes student"s performance, the physical education teachers by interview at SMK Kota Kemuning found that weak students physically and academically suffer from inadequate sleep problems and they are sleepy in the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Iftikhar et al (2014) stated that exercise promotes sleep when fatigue caused by physical activity. The body and mind are easier to sleep and children who are physically active have a higher level self-esteem and a healthy body (Iftikhar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%